Work Accident Risk Control in Road Construction Projects with the Hiradc Approach - Wina Marliana; Sheila Amalia Salma; Bela Pitria Hakim (Jurnal Indonesia Sosial Teknologi, 2024)
Construction projects are a field of work with a high risk of work accidents. CV XYZ, a construction service company, often experiences work accidents on highway projects. These work accidents are caused by human negligence, substandard materials, and inadequate occupational safety and health (OSH) implementation methods. Based on these problems, this study aims to design work accident risk control at CV XYZ to reduce and prevent work accidents on road construction projects. The design of occupational safety and health (OSH) control is carried out by conducting risk analysis on road construction project activities through the HIRADC (Hazard Identification, Risk Assessment, and Determining Control) approach and designing improvements to the occupational safety and health (OSH) control business process. The design of OSH risk control created in this study aims to implement risk control and reduce the risk of work accidents in the company.